Eksplorasi Etnomatematika pada Museum Gedung Juang 45 - Anggraini, Fadhilah dwi; Soebagyo, Joko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this research is to explore the concept of school mathematics in the museum's geometry building to fill the lack of learning resources so that it can be used as a reference for learning. The method in this study uses an ethnographic approach. Data were obtained through thematic analysis, this analysis, and narrative analysis. The results of the study obtained mathematical concepts, namely spatial shapes such as blocks and cone then there are geometric transformations such as translation, reflection, and rotation, the concept of flat shapes such as circle, square and, rectangle. In conclusion, the exploration of the Gedung Juang 45 museum in Bekasi Regency can be a medium for ethnomathematics-based mathematics learning that is contextual and interesting, in line with the three elements of deep learning, namely awareness, meaningful, and fun. Keywords: Ethnomathematics, Gedung Juang 45, Museum